Risk of Subsea Blowouts in Marine CCS - Federica Tamburini; Sarah Bonvicini; Valerio Cozzani (Chemical Engineering Transactions, 2023)
In the foreseeable future, Carbon dioxide Capture and Sequestration (CCS) technique represents a promising method to contribute to the fulfilling of the ambitious objectives of carbon dioxide (CO2) emission reduction posed by the European Commission (EU). The permanent storage of CO2 is a step in the CCS chain that is of great concern due to the possibility of major accidents that could harm both humans and the environment. In the Adriatic Sea, the perspective of reusing depleted natural gas fields to stock CO2 has become more and more appealing since it provides a competitive option to reduce emissions in the short term. With that comes the need to estimate the risk of potential CO2 leakage events, particularly of blowout scenarios, which are one of the main hazards in CO2 injection due to the potential extended duration and high flow rate of the release. Thus, in the present study an assessment of the effects of CO2 blowouts in shallow water has been performed, identifying a set of models and tools available for the analysis of the consequences of subsea gaseous leakages and applying them to specific case studies. The aim of the current investigation is to highlight the specific aspects of the risk profile of CO2 blowouts with respect to those of natural gas, considering that the risk of gas blowouts is not new and has previously been effectively controlled and managed in areas where natural gas reservoirs were exploited.